Equal Learning Does Not Result in Equal Remembering: The Importance of Post-Encoding Processes - Bauer, Patricia J. (Infancy, 2010)
Explanations of variability in long-term recall typically appeal to encoding and/or retrieval processes. However, for well over a century, it has been apparent that for memory traces to be stored successfully, they must undergo a post-encoding process of stabilization and integration. Variability in post-encoding processes is thus a potential source of age-related and individual variance in long-term recall. We examined post-encoding variability in each of two experiments. In each experiment, 20-month-old infants were exposed to novel three-step sequences in each of three encoding conditions: watch only, imitate, and learn to criterion. They were tested for recall after 15 min (as a measure of the success of encoding) and either weeks (1, 2, or 3: Experiment 1) or days (1, 2, or 4: Experiment 2) later. In each experiment, differential relative levels of performance among the conditions were observed at the two tests. The results implicate post-encoding processes are a source of variance in long-term recall.